Exploring the crosstalk between the FGF/FGFR pathway and tumor microenvironment in clear cell renal cell carcinoma - Takafumi Narisawa; Sei Naito; Yoshihide Mitsuda; Rintaro Ohe; Hidenori Sato; Chizuru Kobayashi; Yuki Miyano; Hiromi Ito; Mitsuru Futakuchi; Norihiko Tsuchiya (PLoS ONE, 2026)
Background In the phase 3 CLEAR study, lenvatinib plus pembrolizumab showed improved efficacy versus sunitinib for patients with clear cell renal cell carcinoma (ccRCC). Previous preclinical studies demonstrated that lenvatinib attenuated tumor-associated macrophage (TAM) infiltration into tumor tissues by inhibiting fibroblast growth factor receptor (FGFR). However, the role of the FGFR pathway in ccRCC remains underexplored. This study aims to evaluate FGFR1–4 expression in ccRCC and investigate its relationship with the tumor microenvironment, particularly TAM. Methods We primarily analyzed FGFR1–4 expression and CD163 positive cell count as estimation of TAM infiltration in 57 ccRCC specimens from patients undergoing nephrectomy using immunohistochemistry. Transcriptomic analysis was performed to assess immune-related gene signature and gene expressions. Results FGFR1 expression was elevated in over 80% of ccRCC samples and was significantly associated with increased CD163-positive TAM infiltration. FGFR1 expression was also negatively correlated with the IMmotion150 Teff gene signature and the expression of interferon-γ signaling targeted genes such as IFNG , GZMB , and CD274 , suggesting an immunosuppressive phenotype. In contrast, FGFR2 and FGFR4 expression were less prevalent, and FGFR3 expression was not detected. Conclusions This study provides the first comprehensive evaluation of FGFR1–4 expression in ccRCC and suggests that FGFR1 expression may contribute to the immunosuppressive tumor microenvironment by recruiting TAM. These findings indicate that FGFR1 could serve as a potential biomarker for therapeutic strategies and highlight the need for further research to explore FGFR-targeted therapies in ccRCC.